Effect of TiO2 Nanoparticles and Extrusion Process on the Physicochemical Properties of Biodegradable and Active Cassava Starch Nanocomposites - Iacovone, Carolina Adriana (2023)
Biodegradable polymers have been strongly recognized as an alternative to replace traditional petrochemical plastics, which have become a global problem due to their long persistence in the environment. In this work, the effect of the addition of titanium dioxide nanoparticles (TiO2NP) on the morphology, physicochemical properties and biodegradation under industrial composting conditions of cassava starch-based nanocomposites obtained by extrusion at different screw speeds (80 and 120 rpm) were investigated. Films performed at 120 rpm (S120 and S120-TiO2NP) showed completely processed starch and homogeneously distributed nanoparticles, leading to much more flexible nanocomposites than those obtained at 80 rpm. The incorporation of TiO2NP led to an increase in storage modulus of all films and, in the case of S120-TiO2NP, to higher strain at break values. From the Kohlrausch–Williams–Watts theoretical model (KWW), an increase in the relaxation time of the nanocomposites was observed due to a decrease in the number of polymer chains involved in the relaxation process. Additionally, S120-TiO2NP showed effective protection against UV light, greater hydrophobicity and faster biodegradation in compost, resulting in a promising material for food packaging applications.